SHAPING AMERICA'S PERCEPTION OF MUSLIMS: The Transnational Approach to Globalization’s Role in Popular Culture - Laliyo, Dyah Anastasia Fadhilah; Dewi, Karina Utami (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
After the 9/11 tragedy in 2001, where terrorist attacks destroyed the WTC and the Pentagon, Muslims were widely represented as terrorists in American media. However, the representation of Muslims began to change from 2017 to 2022 in popular culture such as films and TV series. Instead of being depicted as terrorists or